A book in the face of dynamic changes in reality - Podkowińska, Monika (Problemy społeczne: Trwałość i zmienność w dynamicznej rzeczywistości. Księga jubileuszowa z okazji 45-lecia pracy naukowej i dydaktycznej Profesor Jolanty Grotowskiej-Leder, 2022)
In the article, the author presents the place of the book in the communicative world of man, pointing to various forms of writing words and various forms of books that are available to the reader in the context of dynamic changes in reality. The author discusses the communication functions of the book in the context of the information function, self-presentation and exerting influence. It also presents the paper and electronic form of the book, paying attention to the importance of the Internet and crowdsourcing in the context of encoding and decoding messages contained in books. An example of miniature books is also presented, the gathering and collecting of which can be an interesting hobby that allows the implementation of functions related to providing entertainment, relaxation and the development of interests. In the context of miniature books, the author also noted that the books was treated as a kind of talisman. Devoting the article to the issue of books and changes in their forms in the context of the transformations of reality, the author also presented the results of research conducted systematically for almost 3 decades by the National Library, which indicate the level of readership in Poland during the pandemic, but also in the period before the crisis caused by the spread of the SARS-CoV-2 virus.